ОЛИЙ ТАЪЛИМ ТИЗИМИДА ҒОЯВИЙ ТАРБИЯ ИШЛАРИНИ МОДЕРНИЗАЦИЯЛАШ МОДЕЛЛАРИ - Қадиров, Қ.А. (SCIENCE and SOCIETY, 2021)
This article is devoted to modern types, methods and their application, development and effectiveness in the modernization of ideological education in the higher education system in the new Uzbekistan.